Analysis of the Influence of Financial Stability on Accounting Fraud (Farud) and Company Performance Improvement - Nurulia, Eki Tiyas; Juhary, Ali; Suryanto, Tulus (2023)
Accounting fraud has grown in various countries, including in Indonesia. The Indonesian Accounting Association or IAI describes accounting fraud as misstatements arising from fraud in financial reporting and misstatements arising from misappropriation of assets. The tendency of accounting fraud has received a lot of public attention as a concern because accounting fraud can cause losses to other parties and provide benefits for the perpetrators. Even in Indonesia, accounting fraud has become a habit from year to year. The purpose of this study is to analyze the effect of financial stability on the tendency of accounting fraud and increase company performance in food and beverage companies listed on the Indonesia Stock Exchange. With the alleged hypothesis that financial stability has a positive effect on accounting tendencies and financial stability has an effect on company performance. The conclusions in this study are: Financial stability has a positive effect on accounting fraud, which means that the more companies that commit accounting fraud, the more unstable the company’s finances will be, where the company will feel disadvantaged and many companies will go bankrupt. 2. Financial stability has a positive effect on company performance, meaning that with good performance and away from fraud, the company will benefit, where many investors will invest but if the company has poor performance, financial stability will also decrease.